Digital game addiction, anger and aggression among university students - Mehmet Altın (Physical Education of Students, 2025)
Background and Study Aim. The increasing prevalence of digital games and their potential impact on mental health highlight the need to identify protective mechanisms against possible negative effects. This study aims to determine how gender, daily internet use, and age influence digital game addiction, anger expression styles, and aggression levels among university students.